The role of stress coping styles in the relationship between separation individualization and sexual self-schema - Güler, Kahraman; Faraji, Haydeh; Arslan, Gözde (The European Research Journal, 2023)
Objectives: This study aimed to investigate the role of stress coping styles in the relationship between separation individualization and sexual self-schema. Methods: Relational screening model was used in the study. In the selection of the sample group of the study, the convenience sampling method, which is one of the non-random sampling methods, was preferred. The study group of the research consists of 246 (61%) females, 157 (39.0%) males. In this study, Demographic Information Form, Separation Individuation Scale, Sexual Self Schema Scale, and Coping with Stress Scale was used. Results: According to the results, problem-focused coping styles play a partial mediator role in the relationship between separation individuation and loving/compassionate sexual self-schema in coping with stress, and there is a relationship between separation individuation and problem-focused coping styles. Conclusions: There was a significant relationship between separation, individuation and loving/compassionate sexual self and self-confident, optimistic approach, seeking social support. Predicts the compassionate sexual self-schema; It was determined that coping styles were a partial mediating variable in the relationship between relational problems and the loving/compassionate sexual self-schema.